Modern Directions of Intraocular Lenses Improvement. Literature Review - Yu. N. Yusef; G. V. Voronin; A. V. Volzhanin; S. R. Zelimkhanov; E. A. Budnikova; A. Hamdi (Oftalʹmologiâ)
Today, cataract surgery is almost always accompanied with aphakia correction by implantation of an intraocular lens (IOL). In addition to the constant improvement of surgical techniques, special IOLs with improved characteristics are being developed, allowing any optical task to be solved with a minimum of side effects. Since the appearance of the first polymethyl methacrylate IOL, flexible silicone and acrylic IOLs have become available, and the optical design of the lens allows a choice between a single and multiple foci or increased depth of field within a single focus. Optimization of the material, shape and optical design of IOLs remain.